Heimild fyrir gagnagrunnsrannsóknum - Vilhjálmur Árnason (Læknafélag Íslands, Læknafélag Reykjavíkur, 2007)
Hægt er að lesa greinina í heild sinni með því að smella á hlekkinn View/Open It was characteristic of the discussion about the Icelandic Health Sector Database that its proponents laid heavy emphasis on technical security of health care information while the issue of consent for participation in the database was for them of minor significance. It was decided to have a policy of presumed consent which I find flawed from a moral standpoint. However, I do not agree with those critics who have demanded that informed consent for participation in research be obtained. While I think that explicit individual consent is of crucial significance, I argue that the traditional demand for informed consent is neither suitable nor desirable in this case. I argue that different types of consent are appropriate for obtaining genealogical, genetic and health care information that can be connected in database research. I describe an idea of a written authorization based on general information about intended research as an alternative to informed consent and presumed consent for the use of healthcare information. I also propose a more restricted authorization as an alternative to informed consent and open consent to the use of genetic information in database research. Það einkenndi umræður um miðlægan gagnagrunn á heilbrigðissviði að formælendur hans lögðu mikla áherslu á tæknilega upplýsingavernd en gerðu lítið úr þýðingu þess að leita samþykkis þátttakenda í gagnagrunninum. Ákveðið var að ganga út frá ætluðu samþykki þátttakenda sem ég tel hafa annmarka frá siðfræðilegu sjónarmiði. Ég er hins vegar ósammála þeim gagnrýnendum sem halda því fram að afla beri upplýsts samþykkis fyrir færslu gagna í grunninn. Þótt ég líti svo á að afar mikilvægt sé að afla beins samþykkis einstaklinga fyrir gagnagrunnsrannsóknum, þá held ég því fram að hin hefðbundna krafa um upplýst samþykki sé hvorki viðeigandi né æskileg í þessu tilfelli. Ég færi rök fyrir því að mismunandi tegundir samþykkis séu viðeigandi fyrir öflun ættfræðiupplýsinga, ...